Child health during the first coronavirus lockdown in Germany: Fewer treatment cases and fewer diagnoses of infections - Mara Barschkett; C. Katharina Spieß (DIW Weekly Report, 2021)
During the first coronavirus lockdown in Germany in spring 2020, treatment cases of children in outpatient care declined by up to 20 percent. As this study based on administrative diagnosis data of all statutory health insurance companies in Germany shows, there were significantly fewer physical diseases, such as infections, diagnosed in one to 12-year-old children in the second quarter of 2020 compared to 2019. With more than 50 percent, the decline was the largest for one- to two-year-old children. It is possible that actually fewer children became sick due to the contact restrictions and the closure of day care centers and schools. However, it is also possible that in order to avoid the risk of infection, parents took their children to physician's offices less often unless it was absolutely necessary. The reduction in mental illness diagnoses was significantly smaller and the comparably constant figures for chronic diseases such as diabetes or celiac disease indicate that parents with chronically ill children did not forego necessary medical appointments. More attention should be paid to protecting children's health in day care centers and schools in the future, as good health is an important prerequisite for the ability to learn effectively. In addition, more attention should be paid to the current developments in child health, as it seems likely that health aspects, such as mental health, might deteriorate in the course of the pandemic.
Keywords: I10; I14; I20; J13; 330; child health; physical health; mental health; gender; Covid-19